2021
DOI: 10.22454/fammed.2021.341047
|View full text |Cite
|
Sign up to set email alerts
|

Coaching, Mentoring, and Sponsoring as Career Development Tools

Abstract: Background and Objectives: Coaching, mentoring, and sponsoring are tools academic leaders can utilize to develop junior faculty. Each tool has a unique goal, time frame and method. It has been suggested that sponsoring may be a particularly useful tool for furthering the careers of women in medicine. Our primary aim was to understand to what extent one group of academic leaders—family medicine department chairs—have benefited from each tool in their own career development and how often they use each to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…According to Rodenbach et al (2020) , coaching PC conversations could increase health care providers’ preparedness in discussing PC topics and completing goals of care. In contrast, mentoring implies a long period during which the mentor shares their experience and knowledge to help the individual in their development process ( Kowalski, 2019 ; Seehusen et al, 2021 ). Mentoring is typically less structured than coaching, the latter following a more non-directive and rigorous structure.…”
Section: Brief Reviewmentioning
confidence: 99%
“…According to Rodenbach et al (2020) , coaching PC conversations could increase health care providers’ preparedness in discussing PC topics and completing goals of care. In contrast, mentoring implies a long period during which the mentor shares their experience and knowledge to help the individual in their development process ( Kowalski, 2019 ; Seehusen et al, 2021 ). Mentoring is typically less structured than coaching, the latter following a more non-directive and rigorous structure.…”
Section: Brief Reviewmentioning
confidence: 99%
“… Sullivan and Crocitto’s (2007) research has shown that the career change process can be easier for people who are earlier in their career as organizational practice tends to focus career stage learning and development efforts on this population versus those in later career. Elements like coaching and mentoring create a natural accountability toward goals, timeframes, and approaches allowing the individual to make the adjustments needed ( Seehusen et al, 2021 ). This is an iterative process that requires measurement and re-evaluation.…”
Section: Getting Startedmentioning
confidence: 99%
“…A mentor is an individual who can act as a role model, someone to share ideas with, point out blind spots, collaborate on ideas, and can support development and growth ( Seehusen et al, 2021 ). A coach enables individuals to recognize their capability and acts more deliberately by providing performance and behavioral guidance as a periodic practice ( Seehusen et al, 2021 ). A sponsor, however, acts as a career advocate.…”
Section: Preparing To Make the Changementioning
confidence: 99%
See 1 more Smart Citation
“…While there are multiple strategies in the toolbox for career development, Dean Seehusen, MD, MPH, and colleagues in this issue highlight mentoring, sponsoring, and coaching from the experiences of a sample of family medicine department chairs. 1 The majority of these chairs had received career help through these strategies and were using these same approaches with their faculty. They are paying it forward.…”
mentioning
confidence: 99%